EUSTRONGYLIDOSIS’ OCCURENCE IN FRESHWATER FISH FROM THE DANUBIAN DELTA AREA - LAURA URDEŞ; MARIUS HANGAN; CRISTIANA DIACONESCU; DANIELA IANIȚCHI; VLAD SERAFIM (Scientific Papers Animal Science and Biotechnologies, 2023)
The groups of nemathodes who infect fish has been studyied since it has been noticed that these parasites infect a large variety of organisms, being widespread all over the world, in both freshwater and marine species. The aim of this study was to investigate the infections with Eustrongylides sp. in perch, pike, pikeperch, sheat fish, and sun perch, fished into the natural Romanian's lakes, around the Danubian Delta. Our study started on October 2005 and ended on March 2008. The fish have been clinically, pathologically and parasitologically examinated. Following these exams, we have identified the Eustrongylides sp. larvae in muscles, cavity of body and gut in perch, sheat fish and pike; in liver, mesentery and body cavity in pikeperch; into the cavity of body in sun perch. We have also noticed unspecific lesions in these structures, pointing out the presence of circulatory disturbances (congestion and hemorrhage). In perch we have observed the multiparasiting phenomenon, in which Eustrongylides sp. has been found associated with Myxobolus sp., Triaenophorus sp. and Piscicola sp. into the same host.